Restoration of Water Quality in the Estuary Area of Petitenget Beach with the Use of Hydromakrofita Plants - Ida Bagus Suryabrata; Yudha Akbar Prasetyawan; Agus Putu Abiyasa (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Currently, tourist activities around the beach are growing rapidly, especially in the Petitenget Coastal area. Waste management by tourists around the region causes polluted estuary Petitenget Beach. Polluted estuary has an impact on the existing tourism sector, where this results in reduced image of Petitenget beach in the eyes of tourists where tourist activities in the Petitenget area is the main source of income from the Petitenget community. To overcome this problem, it is necessary to restore estuary water, one way is to utilize the potential of The Fragrant Root plant as a fitness agent. From the results of the devotion carried out it is known that the Fragrant Root plant is an effective plant in lowering some polluting parameters, one of which is Ammonia which is the main content of wastewater. The results of this community service will be discussed with the Kerobokan Badung Village and the Badung District Environment and Hygiene Office